“I was very sad, but not depressed”: phenomenological differences between adjustment disorder and a major depressive episode - Zapata-Ospina, Juan Pablo; Jiménez-Benítez, Mercedes; Fierro, Marco (Frontiers in Psychiatry, 2023)
Introduction: Adjustment disorder (AD) is a diagnosis that must be differentiated from major depressive episode (MDE) because of the therapeutic implications. The aim of this study is to understand the experience of patients who in their lifetime have been diagnosed with AD as well as MDE to establish the characteristics of each disorder.Methods: A descriptive phenomenological approach was used with in-depth interviews to four patients and the method proposed by Colaizzi to understand the experiences and reach the description of both disorders.Results: Three women and one man, with advanced schooling were interviewed. The participants emphasized the existence of differences that were grouped in: the attribution made by the individual, the theme of cognitions, the variability in the course, the possibility of mood modulation, the syndrome severity, the presence of hopelessness and the perceived course.Conclusion: Phenomenological differences were found in the subjective experience of MDE and AD. The MDE would be described as an intense state of generalized shutdown of the subject's own life, with little response to events, and the AD, as a dynamic reaction attributed to a stressful event, with high variability in the course of symptoms due to the dependence on such event, with the preserved hope that it will end.